DIAGNOSING THE FORMATION LEVEL OF GRAMMAR COMPETENCE IN STUDYING ENGLISH AFTER GERMAN - Валентина Миськів (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article deals with the results of the research of grammatical competence formation in learning English as a second foreign language. The criteria for evaluation of grammar competence formation and their indices have been highlighted. The article presents structure and essence of grammatical competence of the highest level of mastering it. The results of the pre-experimental research of the level of formation of the intending philologists' grammatical competence in the process of studying English after German have been desribed. Students' initial level of grammar competence in experimental and control groups.